Implementasi Pemanfaatan Teknologi Informasi pada Kebijakan Visa Indonesia - Estheria, Delvina; Dhikadara, Dita; Rahmasari, Ita; Arumdanie, Nisrina; Purwanty, Yunishella (UI Scholars Hub, 2022)
Visa can be used as a migration and population control instrument because visa policy is considered as an efficient way to prevent certain countries from entering the country. Visa policies, especially Indonesian visas, also continue to follow technological developments along with the fulfillment of community needs. This research discusses Indonesian visa policies that are associated with global visas, especially in the field of technology utilization. This research uses a method with a qualitative approach, starting with analyzing visa policies in Indonesia and various countries, then Indonesian Government policies that affect global visa policies and analyzing IT implementation in utilizing visa policies in Indonesia. The results of this study prove that this global visa policy does not only have a negative impact on a country, but can also provide opportunities for countries to develop further. The utilization of information technology in Indonesia's visa policy provides ease of immigration services so that strategic policies are able to attract the arrival of foreign nationals to Indonesia for economic growth in Indonesia in an effort to restore the national economy. On the other hand, this will certainly be a threat and challenge in an effort to maintain organizational resilience and national resilience. Keywords: Visa, Information Technology, Visa Indonesia